1997
DOI: 10.1046/j.1365-2648.1997.1997025434.x
|View full text |Cite
|
Sign up to set email alerts
|

Professional identity: values embedded in meaningful nursing practice

Abstract: The main research question addressed in this two-phase descriptive study was 'What are the values underlying nurses' professional identity as expressed through what is meaningful in nurses' work? The first phase was a survey of 767 randomly selected nurses with one, five, and 10 years of experience in nursing, and in the second phase data on work-meaning were obtained from a convenience sample of six nurses by in-depth interviews eliciting nurses' stories about providing care to patients. Content analysis of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
194
0
10

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(216 citation statements)
references
References 35 publications
12
194
0
10
Order By: Relevance
“…In fact, preceptors have been noted to be the most significant influence in students' perceptions of feeling like an "insider" on a clinical unit [72] and are reported to support students' acquisition of professional values and development of professional identity. [71,73] Preceptors in the current study contributed to positive professional socialization processes by approaching the students early in the preceptorship experience, extending a welcoming demeanor, and demonstrating professional values of collegiality and respect throughout the experience.…”
Section: Discussionmentioning
confidence: 88%
“…In fact, preceptors have been noted to be the most significant influence in students' perceptions of feeling like an "insider" on a clinical unit [72] and are reported to support students' acquisition of professional values and development of professional identity. [71,73] Preceptors in the current study contributed to positive professional socialization processes by approaching the students early in the preceptorship experience, extending a welcoming demeanor, and demonstrating professional values of collegiality and respect throughout the experience.…”
Section: Discussionmentioning
confidence: 88%
“…Identity aspects are generally argued to be positively associated with psychological well-being (Fagermoen, 1997;Karas et al, 2014), and therefore important for recruitment, selection, work motivation, and work engagement. Due to globalization, migration of workers across countries increases, the working environments have and will become increasingly more diverse, which makes work identity an important issue not only for human resource professionals, but also for non-governmental organizations (NGOs) and policy-makers.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Adams and Miller, while exploring the levels of professionalism in Nurse Practitioners (NPs), revealed that 52% of the NPs did not use an ethical framework in their nursing practice and only 12% of the NPs demonstrated their willingness to participate in ethics committee [24] . Knowing the fact that ethical dimension of nursing practice assists nurses in developing their professional identity [64,65] , and impacts the lives of patients, colleagues and society [66,67] , it becomes vital for nurses to apply the code of ethics in their nursing practice. To do so, nurses can reflect on their own values and beliefs and discuss its implications on the ethical dimensions of nursing practice.…”
Section: Ethics and Valuesmentioning
confidence: 99%